Social Media Exposure and Personal Gratification of Students of Elisa R. Ochoa Memorial Northern Mindanao School of Midwifery - Cahilog, Don T. (Randwick International of Social Science Journal, 2024)
The use of social media has been swelling exponentially these past few years and is affecting students in different ways. People use social networking sites, with college students as the most active users. The current study intended to determine the social media exposure of the students and their personal gratification in terms of social and emotional aspects. It made use of a descriptive correlational type of research. Significant statements from clinical instructors and midwifery students were also elicited to get a better glimpse of the extent of social media use in various ways by students. Results showed that social media had beneficial and detrimental effects among the students. The advantages of having faster means of communication and connecting with people in distant places are also damaging to their studies when misinformation takes place. Thus, it is necessary that students will be guided in the choice and use of social media platforms. The findings and significant statements from the respondents of the study served as bases for the formulation of an intervention program on the use of social media for the students.